The pH-dependent Client Release from the Collagen-specific Chaperone HSP47 Is Triggered by a Tandem Histidine Pair - Oecal, Sinan (J Biol Chem, 2016)
Heat shock protein 47 (HSP47) is an endoplasmic reticulum (ER)-resident collagen-specific chaperone and essential for proper formation of the characteristic collagen triple helix. It preferentially binds to the folded conformation of its clients and accompanies them from the ER to the Golgi compartment, where it releases them and is recycled back to the ER. Unlike other chaperones, the binding and release cycles are not governed by nucleotide exchange and hydrolysis, but presumably the dissociation of the HSP47-procollagen complex is triggered by the lower pH in the Golgi (pH 6.3) compared with the ER (pH 7.4). Histidine residues have been suggested as triggers due to their approximate textbook pK(a) value of 6.1 for their side chains. We present here an extensive theoretical and experimental study of the 14 histidine residues present in canine HSP47, where we have mutated all histidine residues in the collagen binding interface and additionally all of those that were predicted to undergo a significant change in protonation state between pH 7 and 6. These mutants were characterized by biolayer interferometry for their pH-dependent binding to a collagen model. One mutant (H238N) loses binding, which can be explained by a rearrangement of the Arg(222) and Asp(385) residues, which are crucial for specific collagen recognition. Most of the other mutants were remarkably silent, but a double mutant with His(273) and His(274) exchanged for asparagines exhibits a much less pronounced pH dependence of collagen binding. This effect is mainly caused by a lower k(off) at the low pH values.